2022
DOI: 10.1186/s43042-022-00253-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 gene intron 3 VNTR polymorphism in adult acute myeloid leukemia

Abstract: Background The proliferation of acute myeloid leukemia (AML) blast into the bone marrow microenvironment is controlled by cytokines. Interleukin-4 (IL-4) has recently been discovered to suppress the development and persistence of AML cells selectively. Intron three of the Interleukin-4 (IL-4) gene contains a 70-bp minisatellite region polymorphism that may influence gene transcriptional activity and subsequently affect the production level of IL4. We investigated the IL-4 gene intron three vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These results provide an interpretation for the decreased level of IL-4 in BC. Moreover, several polymorphisms related to IL-4 encoding gene were shown to be a cancer risk factor ( Ibrahimi et al, 2018 , Shabbir et al, 2022 , Safwat et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide an interpretation for the decreased level of IL-4 in BC. Moreover, several polymorphisms related to IL-4 encoding gene were shown to be a cancer risk factor ( Ibrahimi et al, 2018 , Shabbir et al, 2022 , Safwat et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concertedly with previous studies, 3R/3R genotype of IL-4 VNTR was proven as a protective factor against breast cancer susceptibility in an Iranian population (30) while the effect of IL-4 VNTR variants was not observed in Jordanian breast cancer patients (31). In adult acute myeloid leukemia patients, the frequency of 3R alleles was higher than in controls and 3R/3R genotype was reported to be signifi cantly associated with poor therapeutic response, higher susceptibility to disease recurrence and shorter overall survival and disease-free survival (32). This result was in contradiction with the study of Ahmed et al (33) who reported 2R/2R and 2R/3R genotypes as high risk factors for the development of leukemia.…”
Section: U N C O R R E C T E Dmentioning
confidence: 99%